Reliability of the Sarno river visual assessment protocol (SRVAP) as a river quality education tool result from initial assessment in Aborlan River, Philippines - Macuroy, Jonathan T. (Journal of Human Ecology, 2017)
River water quality monitoring is crucial in the conservation and maintenance of any river system. The extensive requirements, high costs, and complex data makes continuous monitoring difficult. Simpler methods that assess visual characteristics to convey the general quality of the river condition were developed. This study applied the Sarno River Visual Assessment Protocol (SRVAP), a modified version of the Stream Visual Assessment Protocol (SVAP) developed by the United States Department of Agriculture (USDA). The SRVAP, a procedure which utilizes direct observations of the general state of riparian areas, is applied to Aborlan River in the province of Palawan, Philippines. SRVAP reliability as predictors of physicochemical parameters of the river were tested using regression analysis. Results showed that SRVAP is significantly correlated with temperature and total suspended solids (TSS) and can therefore be used as rapid predictors of the physicochemical parameters of Aborlan River. Also, results of the study showed that local knowledge is significant in estimating the values of temperature and TSS.